Comparative law ; a very short introduction - Ragone, Sabrina, 1982-; Smorto, Guido (Oxford : Oxford University Press, 2024)
Sabrina Ragone and Guido Smorto provide a concise introduction to the field of comparative law, explaining how it is used by legislators, judges, international organizations and scholars, and demonstrating that legal comparison challenges conventional beliefs and unquestioned assumptions about law and society.
Also issued in print: 2024.
Includes bibliographical references and index.
Specialized.
Description based on online resource and publisher information; title from PDF title page (viewed on September 29, 2023).
Keywords: Comparative law; Law; Jurisprudence & general issues